PERANAN BANK SYARIAH SEBAGAI INVESTMENT INTERMEDIARY DALAM MENINGKATKAN KESEJAHTERAN MASYARAKAT - Harfandi, Harfandi (Alhurriyah, 2010)
The role of syaria banking as an intermediary investment was required, especially for improving of the prosperity of society, that can be done by implementation of mudharabah financing or musyarakah financing. By channeling the both of this type of financing , all the investment was instructed fully to run the business. Changing and priority in channeling of the bank’s fund are really determine the role of the syaria banking, in the case of improving the development of economics and prosperity of society. By changing the habit of the syaria bank which tend to give loan as a consumptive loan, and replace being a productive loan by using mudharabah or musyarakah willl give the impact to the developer of corporate world, increasing the employment, decreasing of inflation rate, make-up of growth of national product, and improvement of the prosperity of society